HbA1C Variability Is Strongly Associated With the Severity of Cardiovascular Autonomic Neuropathy in Patients With Type 2 Diabetes After Longer Diabetes Duration - Lai, Yun-Ru; Huang, Chih-Cheng; Chiu, Wen-Chan; Liu, Rue-Tsuan; Tsai, Nai-Wen; Wang, Hung-Chen; Lin, Wei-Che; Cheng, Ben-Chung; Su, Yu-Jih; Su, Chih-Min; Hsiao, Sheng-Yuan; Wang, Pei-Wen; et al. (Frontiers in Neuroscience, 2019)
Background: Variability in HbA1c is associated with higher risk of microvascular complications in patients with type 2 diabetes. We test the hypothesis that HbA1C variability is not only strongly associated with the presence but also the degree of severity of cardiovascular autonomic neuropathy (CAN) in patients with a longer duration of diabetes (more than 10 years). Methods: For each patient, the intrapersonal mean, SD, and coefficient of variation (CV) of HbA1c were calculated using all measurements obtained three years before the study. We constructed the composite autonomic scoring scale (CASS) as a measure of the severity of cardiovascular autonomic functions. Stepwise logistic regression and linear regression analyses were performed to evaluate the presence of CAN and influence of independent variables on the mean CASS, respectively. Results: Those with CAN had higher mean age, higher LDL-C, HbA1c-SD, HbA1c-CV, mean HbA1c, and index HbA1c, higher prevalence of retinopathy as the underlying disease, and lower HDL levels. Stepwise logistic regression showed that HbA1c-SD and retinopathy were risk factors that were independently associated with the presence of CAN. Mean HbA1c, HbA1c-CV, HbA1c-SD, and index HbA1c were positively correlated with mean CASS and multiple linear regression analysis revealed that HbA1c-SD was independently associated with the mean CASS. Conclusions: HbA1C variability is strongly associated with not only the presence but also the degree of severity of CAN. Aggressively controlling blood glucose to an acceptable range and avoiding fluctuations in blood glucose by more individualized treatments should be used to reduce CAN progression.